"Right to Repair" vis‐à‐vis Indian trade mark law: A comparative analysis. (16th February 2021) - Arora, Himanshu
Abstract: The prime motive of the present article is to juxtapose the emerging and trending "Right to Repair" with Indian trade mark law to assess or find as to whether the exercise of this "Right to Repair" can tantamount to infringement of a trade mark in accordance with Indian Trade Mark Law, or whether this right is implicitly recognized or hidden in the Indian Trade Mark Law as a defence or an exception to infringement. The article is mainly divided into two parts. The first part would discuss the concept of "Right to Repair" (along with its origins and development in the world and in India), and also attempts to display as to how the IP rights can be used to curtail the scope of this emerging right. While the second part focuses on scrutinizing that as to how this new surfacing right interacts with or muddles through Indian trade mark law, while briefly discussing the two basic types of infringements envisioned under the Trade Mark law and also explaining, in detail, the types of activities which can be undertaken under the garb of this new right.